Epilepsy in tuberous sclerosis complex: Findings from the TOSCA Study. Issue 1 (21st December 2018) - Nabbout, Rima; Belousova, Elena; Benedik, Mirjana P.; Carter, Tom; Cottin, Vincent; Curatolo, Paolo; Dahlin, Maria; D´Amato, Lisa; d'Augères, Guillaume Beaure; de Vries, Petrus J.; Ferreira, José C.; Feucht, Martha; et al.
Summary: Objective: To present the baseline data of the international TuberOus SClerosis registry to increase disease Awareness (TOSCA) with emphasis on the characteristics of epilepsies associated with tuberous sclerosis complex (TSC). Methods: Retrospective and prospective patients' data on all aspects of TSC were collected from multiple countries worldwide. Epilepsy variables included seizure type, age at onset, type of treatment, and treatment outcomes and association with genotype, seizures control, and intellectual disability. As for noninterventional registries, the study protocol did not specify any particular clinical instruments, laboratory investigations, or intervention. Evaluations included those required for diagnosis and management following local best practice. Results: Epilepsy was reported in 83.6% of patients (1852/2216) at baseline; 38.9% presented with infantile spasms and 67.5% with focal seizures. The mean age at diagnosis of infantile spasms was 0.4 year (median <1 year; range <1‐30 years) and at diagnosis of focal seizures was 2.7 years (median 1 year; range <1‐66 years). A total of 1469 patients (79.3%) were diagnosed with epilepsy <2 years. The rate of infantile spasms was higher in patients with a TSC 2 mutation than in patients with a TSC1  mutation (47.3% vs 23%). ɣ ‐aminobutyric acid (GABA)ergic drugs were the most common treatment modality for both infantile spasms (78.7%) and focal seizures (65.5%). Infantile spasms and focal seizures were controlled in 76.3% and 58.2% of patients, respectively. Control of seizures was associated with lower rates of intellectual disability in both groups. Significance: This registry reports the largest international cohort of patients with TSC. Findings confirmed the typical onset pattern of infantile spasms and other focal seizures in the first 2 years of life, and the high rates of infantile spasms in patients with TSC2 mutation. Our results underscored the occurrence of focal seizures at all ages, including an onset that preceded emergence of infantile spasms. Seizure control was shown to be associated with lower rates of intellectual disability but did not preclude the presence of intellectual disability.